Efektivitas rational emotive behavioral therapy dengan teknik self-talk dalam meningkatkan kepercayaan diri siswa untuk berbicara di depan umum - Ayumi, Salsha Nabila; Siregar, Alfin (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
The aim of this research is to determine the effect of self-talk in increasing self-confidence, and to see how effective REBT with Self-Talk Techniques is in increasing students' self-confidence in speaking in public. The research method used by researchers plans to use a quantitative pre-experimental design or experimental approach. The sample was taken using a purposive sampling technique with 13 informants from class 11 majoring in ACP. The research procedure is divided into three stages, namely the first stage is conducting a pretest to measure students' initial level of self-confidence, the second stage is conducting counseling with REBT with Self-Talk Techniques in Increasing Students' Self-Confidence, and the third stage is posttest to see whether After REBT therapy, students will be more confident. Data analysis used the SPSS 25 application. Data analysis techniques used in this research included normality testing, validity and reliability testing, and hypothesis testing. From the results of the research conducted, it can be concluded that the level of confidence in speaking in front of general subjects has increased. From the average (mean) pre-test score, then after receiving REBT with Self-Talk Technique, the post-test score increased. This shows that there was an increase in self-confidence scores. Apart from that, based on the output of the hypothesis test using the paired sample t-test, a significance value of 0.001 (smaller than 0.05) was obtained. This means that self-talk techniques are effective in increasing self-confidence in speaking in public for Al-Washiyah 2 Commerce Private Vocational School students. Therefore, REBT with Self-Talk Techniques is very effective and can be used to increase a person's self-confidence. In implementing self-talk, group members are invited to discuss many important things for themselves. Apart from that, this activity will help you deepen your mind so you can get various interesting ideas. Without realizing it, self-talk has various benefits for mental health. when we start talking to ourselves, it means we understand the situation we are currently experiencing. With positive self-talk, the situation will be processed by oneself to determine the next steps.